Pre-contoured reconstruction plate fabricated via three-dimensional printed bending support - Song, In-Seok; Ryu, Jae-Jun; Choi, Young-Jun; Lee, Ui-Lyong (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2021)
A mandibular continuity defect can be repaired using either a prosthetic device or autogenous bone. A titanium reconstruction plate can be used with a localized or vascularized flap over the defect of the mandible. Unfortunately, the plate may fail due to plate exposure, screw loosening, fracture, or infection, and will need to be removed. Plate exposure though the skin or mucosa is one of the main reasons for failure. In the present work, the authors introduced a lingually positioned reconstruction plate fabricated via three-dimensional printed bending support. This custom reconstruction plate can avoid plate re-exposure as well as reduce surgical errors and operation time.A mandibular continuity defect can be repaired using either a prosthetic device or autogenous bone. A titanium reconstruction plate can be used with a localized or vascularized flap over the defect of the mandible. Unfortunately, the plate may fail due to plate exposure, screw loosening, fracture, or infection, and will need to be removed. Plate exposure though the skin or mucosa is one of the main reasons for failure. In the present work, the authors introduced a lingually positioned reconstruction plate fabricated via three-dimensional printed bending support. This custom reconstruction plate can avoid plate re-exposure as well as reduce surgical errors and operation time.